Language aspects of engineering students' view of entropy. Issue 3 (12th April 2016) - Haglund, Jesper; Andersson, Staffan; Elmgren, Maja
Abstract : Entropy is a central concept in thermodynamics, but has been found to be challenging to students due to its abstract nature and the fact that it is not part of students' everyday language. Interviews with three pairs of engineering students ( N = 6) were conducted and video recorded regarding their interpretation and use of the entropy concept, one year after a course on chemical thermodynamics. From a syntax perspective, students were asked to assess whether different sentences involving temperature, internal energy, and entropy make sense. With a focus on semantics, they were asked to rank a set of notions with regards to how closely they are related to entropy, how scientific they are, and how useful they are for explaining what entropy is. From a pragmatics point of view, students were asked to solve two qualitative problems, which involve entropy. The results show that these chemistry students regard internal energy, but not entropy, as a substance-like entity. The students' ranking of how closely related to entropy notions are and how useful they are for explaining entropy was found to be strongly negatively correlated to how scientific the notions were seen to be. For example, disorder was seen as highly unscientific, but very useful for explaining entropy. In the problem-solving tasks, Chemical Engineering students were comfortable relating entropy to enthalpy and Gibbs free energy, the three notions being seen to form a "trinity" in thermodynamics. However, the students had challenges grasping the unchanged entropy in reversible, adiabatic expansion of an ideal gas, in which they did not consider how entropy relates to the second law of thermodynamics. In final reflections on their learning processes, the students saw weak connections between their problem-solving skills and their conceptual understanding of entropy, although acknowledging that both aspects of learning are important.